2006
DOI: 10.1080/13552600600841631
|View full text |Cite
|
Sign up to set email alerts
|

A risky boundary: Unwanted sexual behaviour among youth

Abstract: The aim of this research was to explore unwanted sexual behaviour amongs young people. Sexual aggression was operationalized at three levels: ''verbal'', ''non-verbal/intimidating'' and ''physically violent''. A total of 1,700 Dutch adolescents completed a questionnaire that included six clusters of possible determinants of unwanted sexual behaviour: background characteristics, personality characteristics, family environment, school environment, friends and deviant behaviour and sexuality and relationships. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 18 publications
1
48
0
Order By: Relevance
“…In a review of research on sexting, Ringrose, Gill, Livingstone, and Harvey (2012) reported that 15% to 40% of young people are involved in sexting, depending on their age and the way sexting is measured. It has been suggested that adolescence is a time of sexual exploration not only in real-life situations but also in the virtual reality of online sex through media such as the Internet, chatrooms, and webcams (de Bruijn, Burrie, & van Wel, 2006). While such practices may be used on a voluntary or mutual basis, sexting may place adolescents at risk of behaviors that are coercive, linked to harassment, bullying, and violence (Ringrose et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In a review of research on sexting, Ringrose, Gill, Livingstone, and Harvey (2012) reported that 15% to 40% of young people are involved in sexting, depending on their age and the way sexting is measured. It has been suggested that adolescence is a time of sexual exploration not only in real-life situations but also in the virtual reality of online sex through media such as the Internet, chatrooms, and webcams (de Bruijn, Burrie, & van Wel, 2006). While such practices may be used on a voluntary or mutual basis, sexting may place adolescents at risk of behaviors that are coercive, linked to harassment, bullying, and violence (Ringrose et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, very little research has focused on the less well-defined experiences, including the more " normative " forms of unwanted sexual attention and behavior, as diverse as verbal (unwelcome sexual jokes or remarks), non-verbal (standing too close to someone, confronting someone with pornographic images), or physically violent (assault) (2) .…”
Section: Introductionmentioning
confidence: 99%
“…There is empirical evidence indicating that partner violence tends to start early in many relationships, and many of these relationships begin during adolescence or young adulthood. However, while many works have considered sexual abuse and sexual violence against adolescents as being perpetrated by adults, less attention has been given to sexual intimidation and unwanted sexual experiences occurring among adolescents (2) . Yet, sexual violence among adolescents is of crucial importance because they are the most at-risk population: they are at the cusp of their sexual life, they often lack self-confidence and do not dare to say no, they are setting up their own boundaries, and are learning to respect those of their peers.…”
Section: Introductionmentioning
confidence: 99%
“…Growing up in an unstable social environment with severe disturbances, and having been the victim of or exposed to sexual and/or physical and emotional abuse during childhood, are factors that have been associated with perpetrators of sexual harassment (Abbey, McAuslan, Zawacki, Clinton, & Buck, 2001; Barbaree & Marshall, 2006;Burton, Miller, & Shill, 2002;P. de Bruijn, Burrie, & van Wel, 2006;Salter et al, 2003;Wekerle et al, 2009;Wolfe, Wekerle, Scott, Straatman, & Grasley, 2004).…”
Section: At-risk Populationsmentioning
confidence: 99%
“…The authors reported that emotional abuse and controlling behaviors (38%), physical abuse (17%), and sexual victimization (14%) were the three most reported types of harassment (Fox, Corr, Gadd, & Butler, 2014). Moreover, Dutch studies suggest that 4%-23% of boys and 18%-36% of girls have experienced some form of physically violent sexual behavior (De Bruijn et al, 2006;De Graaf, Meijer, Poelman, & Vanwesenbeeck, 2005;Dukers-Muijrers et al, 2015). The experience of sexual harassment can lead to a variety of physical, cognitive and emotional problems, such as post-traumatic stress disorder (PTSD), substance abuse, depression, and anxiety (Holmes & Sher, 2013;Kilpatrick et al, 2000Kilpatrick et al, , 2003Van Berlo & Mooren, 2009), and as such, there is a strong need for prevention efforts.…”
Section: Introductionmentioning
confidence: 99%